Rahn Financing Stability amid Macroeconomic Fluctuations: A VECM Analysis of Islamic Pawnshops in Indonesia (2020–2025) - Indra Setiawan Hardiansyah; Fira Nurafini (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The development of rahn financing at Sharia Pawnshops in Indonesia cannot be separated from the dynamics of macroeconomic conditions that continue to change. Macroeconomic instability, such as inflation, BI-Rate, and exchange rates, has the potential to affect the performance and distribution of rahn financing. This condition became more pronounced during the 2020–2025 period, which was characterized by an economic crisis due to the COVID-19 pandemic and the subsequent economic recovery, thus necessitating empirical investigation. This study aims to analyze the effects of inflation, BI-Rate, and exchange rates on the distribution of rahn financing at Sharia Pawnshop in Indonesia, both in the short run and the long run. The analytical method employed in this study is the Vector Error Correction Model (VECM) using time series data. The analysis stages include stationarity tests, optimal lag determination, cointegration tests, VAR/VECM estimation, as well as Impulse Response Function (IRF) and Variance Decomposition (VD) analyses to examine the dynamic relationships among variables. The results indicate that inflation does not have a significant effect on rahn financing. The BI-Rate has a significant and negative effect on rahn financing, suggesting that increases in the benchmark interest rate tend to suppress the distribution of rahn financing. Meanwhile, the exchange rate does not have a significant effect in the short run but shows a significant and positive effect in the long run. These findings indicate that rahn financing is relatively stable against inflationary pressures but is sensitive to changes in the BI-Rate and exchange rate conditions in the long term. This study is expected to provide empirical references for the management of Syariah Pahwnshop and regulators in formulating financing policies that are more adaptive and responsive to macroeconomic dynamics, particularly in maintaining the stability and sustainability of rahn financing in Indonesia.